Safety Zones Around Offshore Installations - Napang, Marthen; Patittingi, Farida; Hambali, Ruslan; Hendrapati, Marcel (International Journal of Global Community, 2019)
In order to protect offshore installations and reduce the risk of accidents, which results in marine pollution, certain areas around offshore installations are designated as exclusion zones and precautionary areas. Article 60 of the United Nations Convention on the Law of the Sea (UNCLOS) of 1982 recognizes the right of coastal states to establish exclusion zones around offshore installations. These zones should extend to a distance not exceeding 500 m from each point of the outer edge of the installation. Also, Resolution A.671(16) of the International Maritime Organization (IMO) (Safety Zones and Safety of Navigation around Offshore Installations and Structures) recommends that governments consider, amongst other things, the establishment of safety zones around offshore installations or structures as well as the establishment and charting of fairways or routing systems through exploration areas. In this regard, this study analyzes the effectiveness of the safety zones prescribed by law in protecting oil installations. It concludes that although UNCLOS 1982 does not stipulate the establishment of safety zones around offshore installations constructed in the territorial sea, the coastal state has a right to establish safety zones in such locations, and its radius may extend beyond 500 m if it is necessary to protect the offshore installation in the territorial sea.